TRANSFORMASI PENDIDIKAN ANAK: STRATEGI DAN TANTANGAN ORANGTUA DALAM MENGASUH ANAK DI ERA DIGITAL - Thorik Aziz; Triana Safira; Denik Arofah S; Selvia Dwi Lusiana; Mutmainnah (QURROTI, 2023)
This research examines the transformation of child education in the digital era, focusing on the strategies and challenges faced by parents in raising their children. The digital era has altered how children learn and interact with the world around them, creating new demands in child-rearing. This study utilizes a library research method to gather data by elaborating on various literary sources, including books, journals, e-books, and other relevant literature. The data analysis technique employed is content analysis of journals and documents accessed through the internet. The research findings indicate that parents encounter various challenges, including monitoring technology usage, fostering digital literacy, and maintaining a balance between online and offline time. Nevertheless, parents also develop diverse creative strategies to support child education in the digital era, such as using educational apps, engaging in open dialogues about social media, and collaborating with schools. This research underscores the importance of parents' role in understanding and addressing these changes, as well as providing a balanced and supportive educational environment for their children. The transformation of child education in the digital era is a dynamic process, and this research provides valuable insights for parents, educators, and relevant stakeholders in effectively addressing these challenges.